The impact of alternative grade configurations on student outcomes through middle and high school - Guido Schwerdt; Martin R. West (Institute for the Study of Labor (IZA), 2011)
We use statewide administrative data from Florida to estimate the impact of attending public schools with different grade configurations on student achievement through grade 10. Based on an instrumental variable estimation strategy, we find that students moving from elementary to middle school suffer a sharp drop in student achievement in the transition year. These achievement drops persist through grade 10. We also find that middle school entry increases student absences and is associated with higher grade 10 dropout rates. Transitions to high school in grade nine cause a smaller one-time drop in achievement but do not alter students' performance trajectories.
urn:nbn:de:101:1-201201107577
Keywords: H52; I21; I28; 330; educational production; public schools; grade configuration; middle schools; high schools; Schulauswahl; Bildungsniveau; Weiterführende Schule; Bildungsökonomik; Florida